Management of Vyanga Vis-A-Vis Melasma Through Ayurveda- A Case Series (International Journal of Ayurveda and Pharma Research, 2022)
Melasma is a skin condition characterized by dark spots and patches on the nose, cheeks, forehead and jaw line. Although it is completely harmless, it causes skin discoloration which is difficult to fade away with routine skin care. Melasma can lead to social isolation and stigmatization adversely affecting the quality of daily life which definitely has a major impact on individual’s psychological state and social relationship.The symptomatology of Vyanga given in various available Ayurvedic classics are Mandala (circular patches), Shyava (brown), Tanu (thin), Niruja (painless), etc. The clinical features of melasma can be correlated with Vyanga and condition can be treated based on the Vyanga Chikitsa.     Objectives: To evaluate the efficacy of Haritakyadi Lepa in the management of Vyanga and to review the etiopathology and the clinical aspect of the Vyanga.Result: Based on the collected data, efforts were made to evaluate the efficacy of Haritakyadi Lepa followed by Sadyo Virechana with Manibhadra Guda in the subjects of melasma vis-à-vis Vyanga.Conclusion: In contemporary science, topical steroids have been described in the management of melasma. Alternative to that Haritakyadi Lepa along with Madhu selected for treatment, has shown very effective result in Vyanga.